Designing the Quality of Emergency Ward Services in Shiraz`s Shahid Faghihi Hospital Based on Quality Function Deployment Method (QFD) in 2011-2012 - S.H Rahimi; M Masoumpour; E Kharazmi; Z Kavousi (Tehran University of Medical Sciences, 2013)
Abstract Background: Hospital Emergency ward plays a pivotal role in hospital and health care system regarding necessity of immediate,qualicative and effective performance due to numerous and complicated processes happens in the emergency ward. QFD is one of the most effective methods used for designing and improving the quality in order to fulfill customers' expectations and improve their satisfaction from provided service. Materials & Methods: This study is aimed to investigate following subjects : 1)identifying the customers' expectations (n=80) and service`s components (n=15) through interviews, 2) defining the relationship between patients' expectations and the service`s components, and also relationship between the service`s component themselves 3) designing the service quality model based on the house of quality diagram" Results: After identifying 13 components of customers' expectations and 20 components of service, 9 components of service were prioritized as parts of service quality model in 3 levels: 1) Physician's office physical environment 2) Improving Nursing performance`s and hospital hotel`s service facilities ,equipping inpatient` room, physician`s room and triage space 3) Improving guide systems, providing adequate welfare for the patients' families, and facilitating the waiting room. Conclusion: The current quality model designed in this study can be a general guide to improve the quality of services provided by the emergency ward. However, using this model has its limitations such as being complex and time-consuming. Key words: QFD, House of Quality, Services of Emergency Ward